Creep Characteristics of Engineering Materials 2020
DOI: 10.5772/intechopen.86078
|View full text |Cite
|
Sign up to set email alerts
|

Creep Characteristics of Engineering Materials

Abstract: The assessment of suitability for further service of the basic material and circumferential welded joints of primary steam pipelines made of 14MoV6-3 steel was made based on the determined characteristics of their mechanical properties and structure. The tests were carried out on materials after service significantly exceeding the design time and 200,000 h. The mechanical properties with respect to the determined class of structure for the basic and welded joint material were compared to the determined class o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…During the service life of the pavement, asphalt is exposed to low temperatures, which tend to alter the rheological behavior. Different studies have concluded that asphalt binder behavior is the dominant component for low-temperature performance of the asphalt pavement mixtures [30]. Therefore, it is very important to study the asphalt binder characterize at low temperatures to have a clear picture of factors that affect the low temperature behavior of pavement.…”
Section: Asphalt Binder Characterization and Tests At Low Temperaturesmentioning
confidence: 99%
See 1 more Smart Citation
“…During the service life of the pavement, asphalt is exposed to low temperatures, which tend to alter the rheological behavior. Different studies have concluded that asphalt binder behavior is the dominant component for low-temperature performance of the asphalt pavement mixtures [30]. Therefore, it is very important to study the asphalt binder characterize at low temperatures to have a clear picture of factors that affect the low temperature behavior of pavement.…”
Section: Asphalt Binder Characterization and Tests At Low Temperaturesmentioning
confidence: 99%
“…As part of the diagnostics, it is necessary to perform the condition assessment not only for the basic material of the components working under creep conditions but also for the material of welded joints. The condition assessment of the welded joint material is necessary to determine the ability of the components to transfer the required service loads during their further service [21][22][23][24][25][26][27][28][29][30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…The main purpose of making such a model is to reduce the costs associated with materials testing of these steels and faster access to the results of calculations. The use of artificial intelligence enables the advancement of stainless steel technology in multiple ways, even though only a small number of definition vectors are available [1][2][3][4][5][6][7]. In recent years, many scientists from around the world have dealt with the topic of the application of artificial intelligence algorithms in material engineering.…”
Section: Introductionmentioning
confidence: 99%
“…2. Isothermal cross-section of the Al-Mg-Si equilibrium plot at solvus solubility temperature [11] As it results from the Al-Si-Mg equilibrium phase diagram, at a concentration above 0.2% Mg, the triple α+Mg2Si+β eutectic crystallises from the liquid. Its equilibrium melting point is ~550°C.…”
Section: Introductionmentioning
confidence: 99%